Konsepsi Uswatun Hasanah Dalam Pendidikan Karakter Siswa - M. Robith Rosfan; Muhammad Nurul Yaqin (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
Focus of this research is how the exemplary method of the teacher (uswatun hasanah) in character education for students of MA Nurul Huda Pakandangan Barat Bluto Sumenep? and how is the implementation of the exemplary teacher method (uswatun hasanah) in character education for MA Nurul Huda Pakandangan Barat students Bluto Sumenep? The approach used by researchers in this study is a qualitative-field approach. Case studies are thorough and in-depth. It is called comprehensive, because what is important is the integrity of the knowledge about the case under study which is a special event in itself, and is called in-depth because case studies are not used to test the truth of a hypothesis, but to explore the truth. The data from this study are the results of interviews with all teachers of the Islamic Boarding School Nurul Huda Pakandangan Barat, Bluto District, Sumenep Regency. The data collection procedure used in this study was an observation interview and documentation. The stages of data analysis in this study include data reduction, including checking and organizing data, displaying data or presenting data and conclusions or verification. Based on the results of the analysis, the authors can draw conclusions from this research that the exemplary method of the teacher (Uswatun Hasanah) in character education for students of MA Nurul Huda Pakandangan Barat Bluto Sumenep includes gentleness, compassion, habituation, quranic stories and sanctions. Meanwhile, the implementation of the exemplary teacher method (Uswatun Hasanah) in character education for MA Nurul Huda Pakandangan Barat students Bluto Sumenep Sumenep includes courtesy, helping attitude, discipline, honesty and religiousness